There Is No Asymmetry of Identity Assumptions in the Debate over Selection and Individuals. Issue 1 (January 2015) - Helgeson, Casey
Abstract : A long-running dispute concerns which adaptation-related explananda natural selection can be said to explain. (The issue is conceptual—not empirical—and orthogonal adaptationism.) At issue are explananda of the form: why a given individual organism has a given adaptation rather than that same individual having another trait. It is broadly agreed that one must be ready to back up a "no" answer with an appropriate theory of trans-world identity for individuals. I argue, against the conventional wisdom, that the same is true for a "yes" answer. My conclusion recasts the landscape and opens the door to a potential resolution.